ANNIVERSARY OF THE GREAT VICTORY AND THE TECHNICOLORED NATURE OF EXTREME DEMOCRACIES - MEDVEDKO, Leonid (CENTRAL ASIA AND THE CAUCASUS, 2005)
The heads of more than 50 of the world’s nations, the U.N. Secretary General, and the leaders of many European and internation-al organizations came to Moscow on 9 May to celebrate the Sixtieth Anniversary of Victory in the Great Patriotic War (1941-1945). This day was a celebration not only for the war veterans, but also for all the nations of the former U.S.S.R. For at that time, they all stood as one to defend and strengthen “the Soviet community of common historical destiny,”1 as Nikolai Vert put it. But the destiny of these nations went on to develop in a way that made it impossible to consolidate their common victory over the Axis Powers. The Soviet Union, which at one time was considered one of the two worlds' superpowers, fell apart before the “Soviet civilization” declared in the 1980s could develop and survive. But even after its collapse, interaction could still be observed through-out the entire former Soviet space between two reciprocal processes—at the state and social levels—which had been developing earlier. The so-called Color Revolutions which followed each other in close succession recently, first in Georgia and Ukraine, and then in Kyrgyzstan, as well as events indicating possible unrest in Uzbekistan, seem to be advancing throughout the entire post-Soviet space. They may also inflict Russia. But today, sixty years after the anti-Fascist coalition sustained its Great Victory over the Berlin-Rome-Tokyo Axis, the common historical destiny of these nations is still being manifested. Admittedly, events today are developing within the framework not of a world war, but of a proclaimed “global” war against international terrorism. This same “war” has been going on longer than the Great Patriotic War and is not a prerequisite or consequence, but rather a background against which these small or Color Revolutions are unfolding. In a conversation with the author of this article, well-known Kyrgyz writer, Chinghiz Aitmatow, characterized them in more precise terms as an explosion of “extreme democracy.”